The Evolving Role of Artificial Intelligence in the Future of Distance Learning: Exploring the Next Frontier - Mijwil, Maad M.; Guma, Ali; Sadıkoğlu, Emre (Mesopotamian Journal of Computer Science, 2023)
In recent years, education has become especially related to the applications provided by artificial intelligence technology through a digital environment that includes a set of tools that assist in processing and storing information. Artificial intelligence techniques contribute to the development of students' skills by providing them with advanced scientific content and building their mental capabilities faster. Moreover, these techniques support analysing student data and suggest suitable educational materials and activities for them. Artificial intelligence is a noteworthy tool for the growth of distance education, especially after the development of expert systems that have become a human advisor in many domains, as this leads to the development of education systems that adjust the level of difficulty of materials based on the student’s performance in the electronic classroom, which ensures that the student continues in education and is not frustrated. This article will review the influential role of artificial intelligence applications in growing distance learning, improving the quality of education, and making it an adaptable and practical environment for students.
Keywords: Distance Learning; Artificial Intelligence; Machine Learning; Education; ChatGPT